ASPECTS THAT INFLUENCE THE QUALITY OF PUBLIC SERVICES FOR PERSONS WITH DISABILITIES IN OBTAINING HUMAN RIGHTS IN INDONESIA - Utami, Angelina Yusi; Arvianti, Eri Yusnita; Rifai, Muhamad (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Public service quality is a public service provided by organizations to serve the needs of people in Indonesia, including people with disabilities. The aim of this research is to identify aspects that influence the quality of public services for people with disabilities in obtaining human rights. The research method used in this article is a literature study by summarizing and examining the extent to which previous studies analyzed phenomena among people with disabilities in achieving human rights and analyzed them comparatively into scientific works. The results of this writing show that the aspects that are a problem are the lack of adequate public services for people with disabilities. Often their rights and obligations are not fulfilled due to various aspects, namely lack of access to information, families closing themselves off so that data is not obtained by the government, being a source of mercy or being used by certain individuals to become beggars and the absence of socialization about people with disabilities to the general public.